Tingkat Pengetahuan Polisi Lalu Lintas Tentang Penanganan Korban Kecelakaan Dengan Cedera Kepala Di Kabupaten Sleman Yogyakarta - Yuninda Kurniawati; Sutono Sutono (PSIK FKKMK UGM, 2017)
Background: Pre hospital patient management is a significant part to decrease early and late death. Head injury in traffic accident victims may increase intracranial pressure which leads to decrease victim’s consciousness. Police officers are the first special responder who may arrive in crashed area. They have responsibility to help the victim.Purpose: The purpose of this study is to know traffic police officer’s knowledge levels about early management of traffic accident victims with head injury at Sleman district in Yogyakarta.Methods: This is descriptive categorical non-experimental study with 97 traffic police officers in Sleman district as subject. We used accidental sampling method of every police station. They filled questionnaire that had been prepared. Univariate analysis with descriptive statistic technique was used to analyse the data.Result: Seventy two of 97 subject (74,23%) had an enough knowledge level of traffic accident victims early management. Fourteen subjects (14,43%) had a good knowledge level, and the others (11,34%) subject have less knowledge level. Conclusion: The traffic police officers had enough knowledge level in early management of traffic accident victims with head injury. ABSTRAKLatar Belakang: Penanganan korban kecelakaan pada area pra rumah sakit dapat menurunkan tingkat kematian pada early dan late death. Pada korban dengan cedera kepala memiliki resiko peningkatan tekanan intra kranial sehingga korban tidak sadarkan diri. Polisi merupakan orang awam khusus yang memiliki kewajiban untuk menolong korban.Tujuan Penelitian: Mengetahui tingkat pengetahuan polisi lalu lintas di Kabupaten Sleman mengenai penanganan korban kecelakaan dengan cedera kepala.Metode: Penelitian ini merupakan jenis penelitian deskriptif kuantitatif non-eksperimental dengan subjekpolisi lalu lintas di Kabupaten Slemanyang berjumlah 97 orang. Subjek diambil dengan accidental sampling di area polsek untuk mengisi lembar kuisioner. Kemudian data dianalisis dengan menggunakan analisis univariat dengan teknik statistik deskriptif.Hasil: Sebanyak 72 dari 97(74,23%) responden memiliki tingkat pengetahuan yang cukup tentang penanganan korban cedera kepala. Sebanyak 14 responden (14,43%) berpengetahuan baik, dan 11 (11,34%) lainnya memiliki pengetahuan yang kurang.Kesimpulan: Tingkat pengetahuan polisi lalu lintas mengenai penanganan korban kecelakaan dengan cedera kepala di Kabupaten Sleman pada tahun 2015 adalah cukup.